Genetic Signatures of Acute Asthma Exacerbation Related With Ineffective Response to Corticosteroid - Kang, Min-Gyu (Allergy Asthma Immunol Res, 2020)
PURPOSE: Acute exacerbation (AE) is an important domain of asthma management and may be related with ineffective response to corticosteroid. This study aimed to find mechanisms of AE using genome-wide gene expression profiles of blood cells from asthmatics and its perturbation by in vitro dexamethasone (Dex)-treatment. METHODS: We utilized lymphoblastoid B cells from 107 childhood asthmatics and peripheral blood mononuclear cells from 29 adult asthmatics who were treated with inhaled corticosteroids. We searched for a preserved co-expression gene module significantly associated with the AE rate in both cohorts and measured expression changes of genes belong to this module after Dex-treatment. RESULTS: We identified a preserved module composed of 77 genes. Among them, expressions of 2 genes (EIF2AK2 and NOL11) decreased significantly after Dex-treatment in both cohorts. EIF2AK2, a key gene acting antiviral defense mechanism, showed significantly higher expressions in asthmatics with AE. The protein repair pathway was enriched significantly in 64 genes which belong to the preserved module but showed no expression differences after Dex-treatment in both cohorts. Among them, MSRA and MSRB2 may play key roles by controlling oxidative stress. CONCLUSIONS: Many genes belong to the AE rate-associated and preserved module identified in blood cells from childhood and adults asthmatics showed no expression changes after in vitro Dex-treatment. These findings suggest that we may need alternative treatment options to corticosteroids to prevent AE. EIF2AK2, MSRA and MSRB2 expressions on blood cells may help us select AE-susceptible asthmatics and adjust treatments to prevent AE.